Differential geometry and topology, discrete and computational geometry - Boucetta, Mohamed; Morvan, J.-M (NATO science series. Computer and systems sciences, 2005)
The aim of this volume is to give an introduction and overview to differential topology, differential geometry and computational geometry with an emphasis on some interconnections between these three domains of mathematics. The chapters give the background required to begin research in these fields or at their interfaces. They introduce new research domains and both old and new conjectures in these different subjects show some interaction between other sciences close to mathematics. Topics discussed are; the basis of differential topology and combinatorial topology, the link between differenti.